Crisis Communication and Reputation Management Frameworks Following Major Organizational Corruption Scandals: A Case Study of the Pakistan Olympic Association: A Study in the Pakistani Sports Governance Context - Muhammad Abdul Jabar Adnan; Muhammad Rashed; Ahmad Raza; Mehmet Dalkılıç; Muhammad Tahir Latif; Hafiza Mustabshara Irfan (Policy Journal of Social Science Review, 2026)
The Pakistan Olympic Association (POA), the country's National Olympic Committee since 1948, has experienced one of the most persistent governance crises in Pakistani sport: a recurring, multi-decade conflict with the state-run Pakistan Sports Board (PSB) over financial accountability, leadership tenure and institutional autonomy that has repeatedly drawn intervention from the International Olympic Committee (IOC) and the Supreme Court of Pakistan. Flashpoints include the 2013 formation of a government-backed rival POA faction that failed to gain IOC recognition, a 2014 Lausanne-brokered settlement, a 2019 Supreme Court ruling affirming POA autonomy, a 2021 blame-game following Pakistan's medal-less Tokyo Olympics performance that drew a formal IOC suspension warning, a 2024 Auditor-General financial audit coinciding with the resignation of 19-year president Arif Hasan, and an eventual PSB-endorsed reconciliation election in December 2024. This article develops and applies a crisis communication and reputation management framework integrating Coombs' Situational Crisis Communication Theory (SCCT) and Benoit's Image Repair Theory to analyze how the POA, the PSB and the IOC communicated through this recurring crisis, and what the eventual 2024 reconciliation reveals about effective reputation-recovery pathways for Pakistani sports governance. A documentary case analysis of real, dated events is combined with an illustrative stakeholder-perception dataset (n = 360). The illustrative analysis indicates that blame-shifting and denial were rated the least effective response strategies, while financial transparency, appeals to constitutional/charter authority, and ultimately negotiated reconciliation were rated most effective, with perceived institutional autonomy and government-federation relationship quality emerging as the strongest predictors of stakeholder trust recovery. The article concludes with a practical crisis communication and reputation management framework for Pakistani national sports governance bodies. Keywords: Crisis Communication; Reputation Management; Situational Crisis Communication Theory (SCCT); Image Repair Theory; Pakistan Olympic Association; Sports Governance Pakistan; Institutional Autonomy; Stakeholder Trust https://doi.org/10.5281/zenodo.21714806